Promotion of trade and Investments between China and India : the case of Southwest China and East and Northeast India - Biswanath Bhattacharyay; Prabir De (Center for Economic Studies and ifo Institute (CESifo), 2005)
Open regionalism and integration between the world's two largest developing countries - the People's Republic of China (China) and India - in trade, investments and infrastructure development can foster outward-oriented development and economic and social benefits that could result in poverty reduction. In view of the increasing trend toward regional integration, particularly the expanded European Union and North American integration, the opportunity costs of not moving toward greater economic integration between China and India involving common neighbouring countries could be increasing. This paper discusses the above subject in the context of possible areas of China - India economic cooperation and integration in the Eastern and Northeastern region of India and Southwestern provinces of China, including neighbouring countries like Bangladesh, Bhutan, Myanmar, and Nepal.
Keywords: F2; F1; R4; Q4; Q1; 330; India; China; economic cooperation and integration; trade; investment and infrastructure development; Internationale Wirtschaftsbeziehungen; Wirtschaftsintegration; Außenhandelsliberalisierung; Direktinvestition; Entwicklung; Wohlfahrtseffekt; China; Indien